2021
DOI: 10.1017/cts.2021.12
|View full text |Cite
|
Sign up to set email alerts
|

Feasibility of a virtual Facebook community platform for engagement on health research

Abstract: Introduction: Community engagement is important for advancing Clinical and Translational Science (CTS), but face-to-face engagement has limited reach and scale. We examined the feasibility of a novel virtual Facebook community platform for public engagement on health research statewide in Minnesota. Methods: The Facebook platform, MN Research Link, was evaluated from June 19, 2019 to June 30, 2020. Facebook advertisements and boosts were used to recruit followers. Content, based on prior formative work, includ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 19 publications
(31 reference statements)
0
5
0
Order By: Relevance
“…To examine how live community events can promote CTS content, a Facebook page, MN Research Link , was developed by the Mayo Clinic (CCaTS) and the University of Minnesota (CTSI) National Institutes of Health–funded CTS Community Engagement Programs. MN Research Link was created to serve as a community platform for public engagement on health research statewide in Minnesota [ 1 ]. The project was deemed exempt by both the Mayo Clinic and University of Minnesota institutional review boards.…”
Section: Methodsmentioning
confidence: 99%
See 4 more Smart Citations
“…To examine how live community events can promote CTS content, a Facebook page, MN Research Link , was developed by the Mayo Clinic (CCaTS) and the University of Minnesota (CTSI) National Institutes of Health–funded CTS Community Engagement Programs. MN Research Link was created to serve as a community platform for public engagement on health research statewide in Minnesota [ 1 ]. The project was deemed exempt by both the Mayo Clinic and University of Minnesota institutional review boards.…”
Section: Methodsmentioning
confidence: 99%
“…Evaluations of pre-existing Facebook communities involved with increasing community engagement and retention have been useful for future researchers interested in disseminating CTS content online [8][9][10]. In a previous program evaluation, our collaborative partnership between the Mayo Clinic (Clinic Center for Clinical and Translational Science [CCaTS]) and University of Minnesota's Clinical and Translational Science Institute (CTSI) evaluated the feasibility of a virtual statewide Facebook community platform to enhance public engagement with health research in Minnesota [1]. Our partnership found that Facebook can be used as a community platform and is feasible in engaging Minnesotan residents in conversations around health and research topics.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations